Prevalence of and Risk Factors for Oral Human Papillomavirus Infection With Multiple Genotypes in the United States. Issue 2 (March 2017) - Bui, Thanh Cong; Tran, Ly Thi-Hai; Thai, Thuy Nhu; Shete, Sanjay S.; Vidrine, Damon J.; Sturgis, Erich M.
Abstract : Background: This study investigated the prevalence of and risk factors for oral human papillomavirus (HPV) infection with multiple genotypes in the United States. Methods: Data were from the nationally representative 2009–2012 National Health and Nutrition Examination Survey. This analysis comprised 9257 participants for whom data on oral HPV (37 genotypes) and associated risk factors were available. Results: The weighted prevalence of multitype (2–6 types) oral HPV infection was 1.5% (2.5% for men, 0.4% for women) in the whole sample and 19.7% (22.0% for men, 12.1% for women) in those who had any type of oral HPV positivity. Most multitype oral HPV cases (83.8%) harbored one or more oncogenic types. In the adjusted multinominal logistic regression model, being male (relative risk ratio [RRR] = 3.69; 95% confidence interval [CI], 1.57–8.65), being a current cigarette smoker (RRR = 2.57; 95% CI, 1.23–5.36), and having a new sex partner in the past year (RRR = 2.10; 95% CI, 1.03–4.28) were associated with an increased risk of multitype oral HPV infection over single-type HPV infection. Conclusions: Men, smokers, and those who had new sexual partners were at a significantly higher risk for multitype oral HPV infection. Abstract : A study using National Health and Nutrition Examination Survey data in the United States found that men, smokers, and those who had new sexual partners were at significantly higher risk for multitype oral human papillomavirus infection.Supplemental digital content is available in the text.